Sex differences in the taste-evoked functional connectivity network. (24th June 2022) - Ponticorvo, Sara; Prinster, Anna; Cantone, Elena; Di Salle, Francesco; Esposito, Fabrizio; Canna, Antonietta
Abstract: The central gustatory pathway encompasses multiple subcortical and cortical regions whose neural functional connectivity can be modulated by taste stimulation. While gustatory perception has been previously linked to sex, whether and how the gustatory network differently responds to basic tastes between men and women is unclear. Here, we defined the regions of the central gustatory network by a meta-analysis of 35 fMRI taste activation studies and then analyzed the taste-evoked functional connectivity between these regions in 44 subjects (19 women) in a separate 3 Tesla activation study where sweet and bitter solutions, at five concentrations each, were administered during scanning. From the meta-analysis, a network model was set up, including bilateral anterior, middle and inferior insula, thalamus, precentral gyrus, left amygdala, caudate and dorsolateral prefrontal cortex. Higher functional connectivity than in women was observed in men between the right middle insula and bilateral thalami for bitter taste. Men exhibited higher connectivity than women at low bitter concentrations and middle-high sweet concentrations between bilateral thalamus and insula. A graph-based analysis expressed similar results in terms of nodal characteristics of strength and centrality. Our findings add new insights into the mechanisms of taste processing by highlighting sex differences in the functional connectivity of the gustatory network as modulated by the perception of sweet and bitter tastes. These results shed more light on the neural origin of sex-related differences in gustatory perception and may guide future research on the pathophysiology of taste perception in humans.